Estrategias metodológicas para la enseñanza de la oración de relativo a estudiantes de español como segunda lengua - Garita Hernández, Flor (2004)
This article develops certain methodological strategies for the teaching of the relative clause in Spanish as a Second Language. Its primary objective is to offer to the instructor of Spanish, the application of a methodological strategy in light of the modern pedagogical theories and methods of Second Language Acquisition and Teaching. The expression of relative clauses has been chosen becacuse it is one of the structures classified as universal, and, in accordance with Chomsky's theories, will be present in the minds of all learners no matter their language background.